Pelatihan Pengenalan Dasar-Dasar Komputer Hardware dan Software - Wawan Budiarto; Deden Rosid Waltam (Lembaga Pengembangan Kinerja Dosen, 2024)
Training in introducing computer basics is one of the trainings that students can develop because the acquisition of excess competencies from this training is quite promising. If students, after becoming alumni, can develop these competencies, it will be very profitable. Partners in this PKM activity are students from MTs Pembangunan Nurul Islam, Sarimulya Setu, South Tangerang. The introductory training on the basics of computer hardware and software was carried out in stages: introduction, counseling and assistance in using it. Based on the results of observations and discussions with partners, there were several problems faced by the introductory training on computer basics, namely students' lack of operating computer technology perfectly, lack of Student motivation when studying computer technology. One of the causes is a lack of awareness of how important it is to study computer technology. The solutions proposed or offered in this PKM activity are as follows: 1. Facilitate and provide direction to MTs students at the school, it is hoped that they can understand the basics of computers more freely without fear. 2. Provide computer basics learning according to level. for junior high school level, they are given advanced material from what they learn formally in school informatics lessons. During training activities, students are encouraged to be able to understand the basics of computers with the aim of raising their self-confidence in learning. For this reason, the PKM team will help to solve problems in the management aspect using training methods